Pengaruh Akuntansi Hijau dan Pengungkapan Lingkungan Terhadap Kinerja Ekonomi dengan Asimetri Informasi Sebagai Variabel Intervening - Vinsent Fernaldi Yulias Sayudha; Nera Marinda Machdar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Economic performance is company performance is needed as a measurement to see the performance and financial health of a company in making investor decisions. This research aims to analyze the influence of green accounting and environmental disclosure towards economic performance with information asymmetry as variable mediation. The population in this research are all of the manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2013 – 2018. The sample selection by using purposive sampling and obtain a sample of 87 companies or 522 observation data. The data analysis method used in this research is multiple linear regression test and path analysis by using Eviews version 9. The result show that green accounting has positive influence on economic performance. Environmental disclosure has positive influence on economic performance. Nothing indirect effect green accounting on economic performance through information asymmetry. Nothing indirect effect environmental disclosure on economic performance through information asymmetry.